Assessment of digital learning objects: survey of investigations in the area of Education - Alexandre, Mariana dos Reis [UNESP]; Barros, Daniela Melare Vieira [UNESP] (Univ Federal Rio De Janeiro, Escola Comunicacao, 2022)
Digital Learning Objects (DLO) are part of the pedagogical possibilities that come with Digital Information and Communication Technologies (DICT) and, with them, concerns arise about the quality and evaluation of ODA. Therefore, the general objective of this article is to know what has been produced about DLO evaluation in the education field. For this, the methodology used was the search and selection of productions related to the theme, the presentation of the content and the results found. The instruments used were descriptors in a Portuguese, English and Spanishspeaking database. With the results obtained, there was a perception of differences between the context of Lusophone investigations and the others. There are parameters for technical evaluations of ODA and there is a need for exploration and development to their pedagogical aspects. Thus, we realize that despite the literature affirming the importance and concern with the evaluation of ODA since the 1980s, investigations on the theme are recent and, still, with great possibility of innovation.
Keywords: Evaluation of digital objects; Digital learning objects; Technology; Digital; Education